(untitled) (Fiep Bulletin - online, 2025)
Introduction: The Brazilian population is aging and generating an increase in the number of comorbidities in sedentary elderly. It is believed that university extension projects to encourage the practice of physical exercise are the solution to maintain or restore the autonomy of the elderly population. Objective: This study aims to present an experience report of the University Extension Project More Health UNAMA in the quality of life of the elderly participants and in the training of students of the Bachelor’s Degree in Physical Education at the University. Methods: This research is characterized by being a descriptive study of the experience report type, about the University Extension Project More Health UNAMA, developed by professors and students from the 4th to the 8th semester of the Bachelor’s Degree in Physical Education at UNAMA Gentil, Belém/PA. Results: Ten elderly people of both sexes were assisted and 26 Physical Education students participated. An improvement in the quality of life of elderly participants was observed, through spontaneous reports, and an improvement in the IPAQ indexes. Regarding the students, there was an improvement in terms of safety in the care of the elderly, since they had the opportunity to apply in practice the contents learned in theory and had the supervision of professors of the course. Conclusion: It was concluded that the project was fundamental for the improvement of the quality of life of the elderly participants and for the training of students and future professionals of Physical Education.